An analysis of unplanned readmissions after head and neck microvascular reconstructive surgery. Issue 12 (December 2020) - Weyh, A.; Nocella, R.; Abdelmalik, M.; Pucci, R.; Quimby, A.; Bunnell, A.; Fernandes, R.
Abstract: The 30-day readmission rate is a highly scrutinized metric of quality surgical care, because readmission is costly and perceived to be avoidable with planning and patient education. Head and neck surgery patients generally have multiple risk factors for readmission, as readmitted patients are generally older, with more co-morbidities, lower socio-economic status, and a history of multiple emergency department visits and readmissions. A retrospective cohort study was implemented to determine the incidence and etiology of 30-day readmission after microvascular head and neck reconstructive surgery, focusing on social risk factors. Data were analyzed by χ 2 test, analysis of variance, t -test, and logistic regression, with statistical significance set at P < 0.05. Of 209 patients included in this study, 35 (16.7%) had a 30-day readmission. Increased needs at discharge were associated with increased readmission, while other social risk factors were less significant for a readmission in this study.